An Empirical Analysis of Appeals by Class Members in Australia's Federal Class Actions. (September 2013) - Morabito, Vince
Australia was one of the first countries to emulate the United States by introducing class actions. But, unlike their American federal counterparts, the drafters of the three class action regimes that are in operation in Australia chose to deal expressly with and regulate the ability of class members (who are bound by, but not formal parties to, the class action litigation) to file an appeal, where the class representative is unwilling or unable to take such a step, from judicial orders that are adverse to their interests. Despite the fact that the ability to file an appeal represents one of the most significant powers available to Australian class members to ensure that their interests are protected in the litigation (without the involvement of the class representatives), these appeal mechanisms have not been the subject of critical analysis by Australian scholars. The aim of this paper is to address this lacuna in the legal literature by reviewing the aims, essential features and operation of the provision that governs the ability of class members to file appeals in Australia's longest running class action regime, which has been regulating class actions in the Federal Court of Australia since March 1992. For this purpose, the findings that have emerged from the first-ever empirical study of this regime, which the author recently conducted, are employed. References are also made to the corresponding provisions found in the two other Australian class action regimes, which operate in the Supreme Courts of Victoria and New South Wales, and to the American and Canadian experience with appeals by class members.